European approaches for investment regulation in Ukraine - Layko, Oleksandr (Видавництво Львівської політехніки, 2013)
the prospects of implementation of European approaches to the regulation of the investment process in Ukraine are considered. According to the modern tendencies of preferential transfer of capital investment process to the revenue-generating and self-recouping activities the main emphasis is made on supporting of reproductive processes in strategically significant commodity markets. The European approaches to decentralization of the investment process and the granting of state guarantees to investors are considered as the main factors for funding activation and support of financial capital reproduction that is to be provided by government as a cause of readiness to the European integration. Implementation of regional management approaches in the investment environment is offered by the help of governmental leverages of tax and regulatory policies.
Keywords: European approaches for investments management; management of regional investments; local governance of investment activities; stimulation of capital reproduction in significant commodity markets